Manajemen Produksi Sumber Daya Manusia Dalam Pengembangan Produk Pembiayaan Halal di Bank Syariah - Andi Yuniarti; Novianti; M. Zhali (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2024)
Human resource (HRM) management plays a strategic role in the development of halal financing products in the Islamic banking sector. This study aims to analyze how HRM production management is applied in the creation and development of halal financing products and to identify challenges and optimal solutions. The method used is descriptive qualitative, based on field and literature studies. The study results indicate that HRM management in Islamic banks includes a recruitment strategy based on Sharia values, ongoing training on muamalah jurisprudence, and collaboration between HRM, product teams, and the Sharia Supervisory Board (SSB). However, obstacles remain, such as limited HRM with a balanced mastery of Sharia and innovation aspects, as well as an incentive system that does not optimally support innovation. Optimization of HRM management is carried out through integrated training, redesigning the incentive system, and developing an integrated competency map. The implementation of effective HRM management has an impact on increasing the ability to innovate halal products and maintaining compliance with Sharia principles, ultimately strengthening the competitiveness of Islamic banks in the financial market.